Economic risks of agricultural enterprises in Ukraine: Analysis of threats and mitigation strategies to ensure financial security - Denys Pylypenko; Nataliya Shevchenko; Maksym Pylypenko (Economic Forum, 2025)
The study aimed to identify economic risks, in particular the impact of currency fluctuations, inflation and changes in tax policy on the financial security of Ukrainian agricultural enterprises. The data of such companies as Myronivsky Hliboproduct, Kernel and Slobozhansky Agrocombine were studied. Comparative analysis methods were used to assess the impact of macroeconomic factors on the agricultural sector. For this purpose, the situation in Ukraine and Germany, which is an example of a stable economy in the European Union, was compared. The study identified key economic threats to agricultural enterprises, including currency fluctuations, inflation and high lending rates. The study determined that in 2022, the hryvnia exchange rate experienced significant fluctuations, which made it difficult to import agricultural inputs and increased production costs. The stabilisation of the exchange rate in 2023 was analysed, but in 2024, amid rising inflation of 12%, currency instability again created difficulties for farmers, in financing imports. In general, in 2025, new tax initiatives were also introduced, including a reduction in the value-added tax for small and medium-sized businesses from 20% to 10%, which helped ease the financial burden on farmers. However, large enterprises remained subject to the high corporate tax rate of 18%, which increased their costs and reduced their competitiveness. The study also revealed the effectiveness of government and international financial initiatives, such as the “Affordable loans 5-7-9%” programme, the United States Agency for International Development Agro, the European Innovation Council Accelerator, as well as projects of the European Union and the World Bank aimed at supporting the agricultural sector during economic instability. These initiatives provided agricultural enterprises with access to finance, reducing the risks associated with high interest rates and currency fluctuations. The practical significance of the study is to develop strategies to minimise economic risks for Ukrainian agricultural enterprises, which contributes to their financial security and increases the sector's resilience through business diversification and the introduction of digital technologies
Keywords: 330; investments; monitoring; anti-crisis mechanisms; diversification; lending